Quality of Life in Teenagers and Adults With Coeliac Disease: From Newly Spanish Coeliac Disease Questionnaire Validation to Assessment in a Population-Based Study - Moreno, María de Lourdes; Sánchez-Muñoz, Diego; Sousa, Carolina (Frontiers in Nutrition, 2022)
Background Coeliac disease (CD) is an immune-mediated systemic disorder elicited by the ingestion of gluten in genetically predisposed individuals. Gluten restriction in CD sufferers leads to numerous limitations in various aspects of daily life and can significantly impact the quality-of-life (QoL). The specific and widely used Coeliac Disease Questionnaire (CDQ) is an excellent tool to evaluate QoL in patients with CD, assessing physical, psychological, and social domains. This questionnaire is unavailable in Spain. Therefore, our study is the first to translate, culturally adapt, validate, and apply the Spanish version of CDQ to a representative sample of Spanish teenagers and adults with CD. Methods A total of 153 CD participants with biopsy-proven and self-reported gluten-free adherence were included in the cross-sectional study, which included four stages: (1) translation and retranslation of the French CDQ version into Spanish; (2) cultural adaptation and semantic evaluation; (3) CDQ validation through the internal consistency determination and reproducibility of the QoL; and (4) application of the questionnaire to Spanish teenagers and adults with CD and estimation of QoL using EQ-5D. Results The internal consistency and test–retest reliability of the Spanish CDQ were satisfactory and no ceiling or floor effects were detected. Significant correlations were identified between the CDQ scales, and the instrument for validation covering similar dimensions of the QoL was identified. The mean CDQ total score was 131.03 ± 24.1, and the social domain had the highest rating. There was no correlation between the time spent on a gluten-free diet and QoL. A significantly higher QoL score was reported among males and adolescents in the 15–17 age groups. Conclusion The newly Spanish CDQ is an appropriate tool to assess the QoL of the teenager and adult patients with CD. This study highlights the importance of identifying the affected scales to address actions to reduce the impact of the gluten-free diet burden of the coeliac patients and maintain public health regulations that support patients with chronic diseases such as CD.